The Impact of Radiation Dose on Preoperative Neoadjuvant Chemoradiotherapy Effects for Patients with Locally Advanced Squamous Cell Esophageal Carcinoma: A Propensity Score-Matched Retrospective Study - Yanru Mu; Hui Wang; Tao He; Li Xu (Journal of Immunology Research)
Objective. To explore the impact of radiation dose on preoperative neoadjuvant chemoradiotherapy effects for patients with locally advanced squamous cell esophageal carcinoma (LASCEC) with long-term follow-up data. Methods. The patients with LASCEC received either low dose radiotherapy (50.4Gy/23f/1.8Gy) or a high dose (64.8Gy/25f/1.8Gy) followed by neoadjuvant chemotherapy preoperatively were included in this study. To balance potential bias, 1 : 1 propensity score matching (PSM) with a caliper of 0.1 was used. The two groups were compared in terms of radical resection, post-radiation adverse event rates, perioperative mortality, postoperative adverse event rates, overall survival (OS), local recurrence rate, and distant metastatic rate. Results. Forty-two patients were enrolled in this study, with 21 patients in each group after PSM. There was no difference in baseline characteristics between the two groups (all p >0.05). The rates of radical resection (71.4% vs 57.1%, P =0.334), perioperative mortality (9.5% vs 4.8%, P =0.549), and postoperative adverse event rates (76.2% vs 90.5%, P =0.410) did not differ significantly between the two groups. The 5-year OS rate was statistically higher in the group with a high dose (66.7% vs. 28.6%, P =0.013). Meanwhile, the local recurrence rate was statistically lower in the high dose group (14.3% vs 47.6%, P =0.019 for 3 years; 33.3% vs 66.6%, P =0.031 for 5 years). Moreover, the 3-year distant metastasis rate was statistically lower in the group with a high dose (9.5% vs 38.1%, P = 0.03). Conclusion. Patients with LASCEC may benefit from preoperative neoadjuvant chemoradiotherapy with a high radiation dosage (64.8Gy/25f/1.8Gy).